A multicenter randomized phase II trial of hyperthermia combined with TPF induction chemotherapy compared with TPF induction chemotherapy in locally advanced resectable oral squamous cell carcinoma. (1st January 2021) - Ren, Guoxin; Ju, Houyu; Wu, Yunteng; Song, Hao; Ma, Xuhui; Ge, Minghua; Qiu, Weiliu; Chen, Yazhu; He, Yue; Zhuang, Qianwei; Meng, Jian; Guo, Wei
Abstract: Background: Hyperthermia has been reported to cause cancer stage regression, thus providing surgical opportunities in patients with unresectable tumors and improving the quality of life of patients by preserving certain organs. Methods: A prospective open-label phase II trial was conducted to evaluate the efficacy of hyperthermia combined with induction chemotherapy in patients with locally advanced resectable oral squamous cell carcinoma (OSCC). Patients received hyperthermia combined with two cycles of 5-fluorouracil, cisplatin, and docetaxel (TPF) induction chemotherapy regimens or TPF induction chemotherapy alone, followed by radical surgery with postoperative radiotherapy. The primary endpoint was the clinical response rate of the induction chemotherapy. The secondary endpoints were overall survival (OS), disease-free survival (DFS), and toxicity. Results: A total of 120 patients were enrolled, and 115 patients were included in the clinical response analysis. The clinical response rate was significantly higher in the experimental arm than in the control arm (65.45% vs. 40.00%, p  = 0.0088). There were no unexpected toxicities, and hyperthermia and induction chemotherapy did not increase the perioperative morbidity rate. Moreover, there was a significant improvement in DFS, but no significant difference in OS between the two arms. In the subgroup analysis, increased OS and DFS rates were associated with patients with favorable clinical response after induction chemotherapy in the total population, experimental arm, and control arm. Conclusions: Our study demonstrates that hyperthermia combined with induction chemotherapy is associated with a high response rate and provides a new treatment option for patients with resectable stage III or IVA OSCC.